Developing a Specialized Service Quality Model for Universities. Issue 3 (3rd July 2019) - Fazli-Salehi, Reza; Esfidani, Mohammad Rahim; Torres, Ivonne M.; Zúñiga, Miguel Angel
Abstract: Given the important role of universities in economic, social, cultural, and political dimensions, it is vital to ensure optimal quality of their performance in order to prevent loss of human and material capital and to maximize their competitiveness. This study develops a model for assessing perceived quality of universities and explains the outcomes of perceived quality among students. Results show that quality of lecturers, prestige, connection with outside world, extra-curriculum activities, research potential, responsiveness, facilities, design and ambiance, and diversity are considered components of perceived quality. Students with higher perceived university quality will make greater efforts to grow the brand.